HUBUNGAN ANTARA KELEKATAN AMAN DENGAN KOMPETENSI SOSIAL PADA SISWA PENDATANG DI SMA KRISTEN SATYA WACANA SALATIGA - RISKA PUTRI YULIANTI; Ika Febrian Kristiana (Jurnal EMPATI, 2017)
Social competence allows students from outside the town to be able to adapt towards the various changes experienced in self and the environment. This study aims to examine the relationship between secure attachment and social competence of new comer student in SMA Kristen Satya Wacana Salatiga. The population in this study is 114 students from 10th and 11th year of science, social and language class with the sample of 105 students. The sampling technique was using the saturated sampling method. The collecting data method used is the secure attachment scale (27 item, α = .883) and the social competence scale (20 item, α = .809). The result of Spearman’s method showed the simple regression coefficient rxy = 0.584 with  p<0.005. The result proves that hypothesis is accepted, there is a positive relation between secure attachment with social competence of new comer student in SMA Kristen Satya Wacana Salatiga.